A transcriptional regulatory module controls lipid accumulation in soybean. Issue 2 (25th May 2021) - Lu, Long; Wei, Wei; Li, Qing‐Tian; Bian, Xiao‐Hua; Lu, Xiang; Hu, Yang; Cheng, Tong; Wang, Zhou‐Ya; Jin, Meng; Tao, Jian‐Jun; Yin, Cui‐Cui; He, Si‐Jie; et al.
Summary: Soybean ( Glycine max ) is one of the most important oilseed crops. However, the regulatory mechanism that governs the process of oil accumulation in soybean remains poorly understood. In this study, GmZF392, a tandem CCCH zinc finger (TZF) protein which was identified in our previous RNA‐seq analysis of seed‐preferred transcription factors, was found to function as a positive regulator of lipid production. GmZF392 promotes seed oil accumulation in both transgenic Arabidopsis and stable transgenic soybean plants by binding to a bipartite cis ‐element, containing TG‐ and TA‐rich sequences, in promoter regions, activating the expression of genes in the lipid biosynthesis pathway. GmZF392 physically interacts with GmZF351, our previously identified transcriptional regulator of lipid biosynthesis, to synergistically promote downstream gene expression. Both GmZF392 and GmZF351 are further upregulated by GmNFYA, another transcription factor involved in lipid biosynthesis, directly (in the former case) and indirectly (in the latter case). Promoter sequence diversity analysis showed that the GmZF392 promoter may have been selected at the origin of the Glycine genus and further mildly selected during domestication from wild soybeans to cultivated soybeans. Our study reveals a regulatory module containing three transcription factors in the lipid biosynthesis pathway, and manipulation of the module may improve oil production in soybean and other oilseed crops.